2013
DOI: 10.1002/anie.201207548
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Transition‐Temperature Mixtures (LTTMs): A New Generation of Designer Solvents

Abstract: A new generation of designer solvents emerged in the last decade as promising green media for multiple applications, including separation processes: the low-transition-temperature mixtures (LTTMs). They can be prepared by mixing natural high-melting-point starting materials, which form a liquid by hydrogen-bond interactions. Among them, deep-eutectic solvents (DESs) were presented as promising alternatives to conventional ionic liquids (ILs). Some limitations of ILs are overcome by LTTMs, which are cheap and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
753
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,161 publications
(760 citation statements)
references
References 70 publications
4
753
0
3
Order By: Relevance
“…They may also be classified as designer solvents since their structures can be adjusted by selecting the hydrogen-bond donoreacceptor combinations, tailoring their phase behavior and physical properties [4]. Moreover, it was shown that addition of agents able to break the DES complex allows recrystallization and recovery of one or both of the initial components, since these remain in their molecular state upon melting [5,6]. DES exhibit a wide range of properties which make them an attractive family of solvents for different applications in catalysis, organic synthesis, dissolution and extraction processes, electrochemistry and material chemistry [2e5, 7,8].…”
Section: Introductionmentioning
confidence: 99%
“…They may also be classified as designer solvents since their structures can be adjusted by selecting the hydrogen-bond donoreacceptor combinations, tailoring their phase behavior and physical properties [4]. Moreover, it was shown that addition of agents able to break the DES complex allows recrystallization and recovery of one or both of the initial components, since these remain in their molecular state upon melting [5,6]. DES exhibit a wide range of properties which make them an attractive family of solvents for different applications in catalysis, organic synthesis, dissolution and extraction processes, electrochemistry and material chemistry [2e5, 7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2,3,4,5] Historically, researches about DESs are related to the Ionic liquids (ILs) that are organic salts with a low melting point (<100°C) combining an organic cation with an organic or inorganic anion. [6,7,8,9,10] DESs and ILs have both attractive physical properties: they are non-volatile, non-flammable and their solvent properties could be tailored by designed functions, therefore the considered applications of DESs or ionic liquids are often similar.…”
Section: Introductionmentioning
confidence: 99%
“…Abbott et al have reported the first associations between choline chloride and natural compounds such as urea in 2003. [3] A C C E P T E D M A N U S C R I P T 2 Associations in DESs could involve different interactions such as hydrogen bonds between a hydrogen-bonding donor (HBD) and a hydrogen-bonding acceptor (HBA). The choice of the components to form a DES is thus immense as DES could associate one to several compounds in different proportions.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, Abbott et al presented a new class of solvents-deep-eutectic solvents (DES). A DES is a mixture of two or more compounds with a melting point lower than its individual components that includes both a quaternary ammonium salt as a hydrogen bond acceptor (HBA) and a hydrogen bond donor (HBD) that associate with each other by hydrogen bonding (Abbott et al 2003;Francisco et al 2013, Shishov et al 2017. Recently, Dai et al (2013) reported the preparation of several DES reagents of natural origin termed natural (Dai et al 2013;Choi et al 2011).…”
Section: Introductionmentioning
confidence: 99%